Program Kerja Badan Kesbangpol dan Linmas Dalam Pengembangan Wawasan Kebangsaan Provinsi Jawa Tengah Tahun 2016 - Sembiring, Nota Vianta; Isdaryanto, Noorochmat; Suhardiyanto, Andi (Unnes Political Science Journal, 2017)
Indonesia is a very diverse , so vulnerable to conflict in the community . Conflicts occurred in indonesia is religion conflict and terrorism by the radical. One of the provinces in indonesia with the number of cases related high religion conflict and terrorism is provincial central java , because last year 2016 according to the social studies and religion semarang ( elsa ) is 20 a case that occurred . Seen from the number of religion conflict and terrorism , it can be summed up the community in the central java has made their faded nationality insight. Indonesia has a special institution deal with associated nationality insight the national unity political and protect people.